Penerapan Pendidikan Karakter Peduli Lingkungan Melalui Program Adi Wiyata di SMK Negeri Kalibaru Sebagai Upaya dalam Mendukung Gerakan Banyuwangi Merdeka Dari Plastik - Harjianto Harjianto; Rohmatul Fitria Febyanti; Yuli Kartika Efendi (Universitas Batanghari Jambi, 2021)
Human life is closely related to the environment but still lacks a sense of concern and responsibility for the environment, so it is necessary to implement character education caring for the environment. Character education that cares for the environment is a process of developing a conscious attitude as part of the environment, so that it seeks to prevent and repair damage to nature and strive to preserve the environment for future generations. The purpose of this study was to determine how the implementation of character education caring for the environment through the Adiwiyata Program for Kalibaru State Vocational High School students in the success of the Banyuwangi Merdeka Program from Plastics. The research method used in this research is qualitative. The subjects in this study were the principal, educators and students. Data collection was carried out by observation techniques, interview techniques, and documentation techniques. The data analysis technique used is an interactive analysis technique which includes data collection, data reduction, data presentation, then drawing a conclusion. The results showed that character education caring for the environment through the Adiwiyata program was in line with the Banyuwangi Regency government program, namely freedom from plastic and the program was running well. The program of activities includes clean Friday, healthy Friday, taqwa Friday, daily and weekly routine pickets and programs free from plastic waste. In addition, it also limits the sale of food using plastic media, and urges school residents to bring food and drink containers from home. Through this program, students care more about preserving and cleaning the environment. This is evident from the clean and beautiful conditions of the Kalibaru State Vocational School environment.